Tuning the Color Temperature of White‐Light‐Emitting Electrochemical Cells by Laser‐Scanning Perovskite‐Nanocrystal Color Conversion Layers. Issue 4 (12th December 2017) - Wu, Wen‐Kuang; Wang, Cheng‐Ming; Chan, Ming‐Che; Lien, Jiun‐Yi; Su, Yong‐Ming; Sarma, Monima; Yang, Zu‐Po; Su, Hai‐Ching; Wong, Ken‐Tsung; Wang, Sue‐Lein
Abstract: The development of white‐light‐emitting electrochemical cells (LECs) has attracted great attention owing to their numerous advantages. Recently, perovskite materials have also shown many outstanding optoelectronic properties in light absorption and emission, and hence they are suitable for serving as the color conversion layers (CCLs) in solid‐state white‐light‐emitting diodes (LEDs). Here, white LECs were fabricated by integrating non‐doped blue‐green LECs with CCLs made of a single composition of perovskite nanocrystal (NCs). Moreover, the correlated color temperatures (CCTs) of the white LECs can be tuned by modifying the optical properties of the perovskite NCs, in the same way as so as the color conversion properties of CCLs are tuned, through laser scan. By controlling the laser power, scanning number, and duty cycle of the scanned grating patterns on perovskite‐NC CCLs, the CCTs of the white LECs can be tuned from 2502 K to nearly 4300 K. Since this method is much different from that used with conventional CCLs, which use multiple compositions of perovskite NCs to produce white light, the inherent anion‐exchange issue of perovskite NCs can be avoided. Abstract : Tuning light : A laser‐scanning technique was used to modify the color conversion properties of perovskite nanocrystals acting as the color conversion layer in white‐light‐emitting electrochemical cells (LECs). By controlling the scanning conditions, the correlated color temperature of white LECs can be tuned widely (see figure).